PENGARUH INTENSIFIKASI DAN EKSTENSIFIKASI PEMUNGUTAN PAJAK PARKIR UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA SURABAYA - Fransisca, Anggie; murgianto, murgianto (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of tax collection intensification and extensification parking to increase local revenue in the city of Surabaya. The research uses a quantitative approach with case studies. And the data used by this study is primary data obtained from distributing questionnaires to respondents or a parking attendant in one of the parks in the city of Surabaya with a total of 30 respondents (parking attendants). The data analysis technique used is Multiple Linear Analysis using the T-test, F-test, and the Coefficient of Determination with the help of SPSS. The research shows the results of the T-test hypothesis testing can be concluded that the intensification T-test is 3.340 > T-Table 2.045. So it was decided that Ho was rejected and Ha accepted. then intensification has a positive and significant effect on regional income. And for the extensification of the Value of 3,632 > 2,045, it is decided that Ho is rejected and Ha is accepted, then the extensification has a positive and significant effect on regional income